Literasi Budaya Pada Mitos Cerita Legenda "Bulusan" Sebagai Nilai Moral - Lokalitas Kudus - Dinda Permata Sari; Adeena Iluh Maharani; Lisa Noor Amelia (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this research is to help and make it easier for the community, especially elementary school children, to understand the folklore of Bulusan. The research subject is located in Dukuh Sumber, RT 04 RW 05, Hadipolo Village, Jekulo District, Kudus Regency, with its legacy which still exists today, namely the existence Bulus animals, Bulus pond, Mbah Dudo's grave. The method used in this study is qualitative research with qualitative descriptive analysis methods, namely data analysis techniques carried out in this study analyzing all information obtained from various sources and through observation, interviews, recording and recording data. The relationship between folklore and literature is very close. Socio-cultural products always contain socio-cultural values ​​and moral norms that are in line with the views of the creators and a system of values ​​and moral standards that are understood by the creators, originating from the socio-cultural conditions that surround the creators. That is why folklore in literature always reflects the social values ​​and norms of society, namely the moral values ​​and norms that the author adheres to.